Pretreatment of carbon nanotubes: Effects on its properties and catalytic performances - Sulong, T.S.T. (American Institute of Physics Inc., 2016)
The effects of pretreatment via acid and thermal treatment on the properties of multi-walled carbon nanotubes (MWCNTs) are studied using FTIR, TGA, Raman spectroscopy and TEM. Meanwhile, catalytic performances of Cu/ZnO catalysts supported on raw and treated CNTs are evaluated by CO2 hydrogenation into methanol using a fixed-bed microactivity reactor. Pretreatment of CNTs have removed caps, created defects on CNTs wall and also introduced some functional groups as confirmed by FTIR, TGA, Raman spectroscopy and TEM. However, deposition of metals into the support via incipient wetness impregnation method results in agglomeration of metal particles outside CNTs. Methanol synthesis studies (523 K, 22.5 bar) were performed and activity study revealed that catalysts supported on treated CNTs achieved CO2 conversion of 19 . Â© 2016 Author(s).